2022
DOI: 10.1101/2022.04.28.489853
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Highly efficient genome editing in barley using novel LbCas12a variants and impact of sgRNA architecture

Abstract: We report the first successful, high efficiency use of LbCas12a in barley and describe the development and application of two novel Cas12a variants. In total we compared five coding sequence (CDS) variants including the two novel ones and two guide architectures over 5 different target genes using twenty different guides. We found large differences in editing efficiencies between the different CDS versions (0-87%) and guide architectures (0-70%) and show our two novel CDS versions massively outperform the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Taken together, our results demonstrate that the introduction of introns into the coding sequence of tt Lb Cas12a dramatically improves both gene editing and gene targeting in Arabidopsis , so that even heterochromatic and other hardly accessible targets become editable. In an independent study, it has very recently been shown that the addition of 8 introns into the ttLbCas12a coding sequence can enhance editing efficiencies in barley (Lawrenson et al ., 2022 ). Thus, in general, the inclusion of introns into ORFs of Cas nucleases seems to be a very promising way to enhance the editing efficiency in mono‐ as well as dicotyledonous plant species.…”
mentioning
confidence: 99%
“…Taken together, our results demonstrate that the introduction of introns into the coding sequence of tt Lb Cas12a dramatically improves both gene editing and gene targeting in Arabidopsis , so that even heterochromatic and other hardly accessible targets become editable. In an independent study, it has very recently been shown that the addition of 8 introns into the ttLbCas12a coding sequence can enhance editing efficiencies in barley (Lawrenson et al ., 2022 ). Thus, in general, the inclusion of introns into ORFs of Cas nucleases seems to be a very promising way to enhance the editing efficiency in mono‐ as well as dicotyledonous plant species.…”
mentioning
confidence: 99%
“…We already achieved e cient Cas12a mutagenesis in the CDS comparison above using a ribozyme-based guide architecture we designate as version 2 (V2). Previously we tested a version 1 (V1) architecture which relies on the innate processing activity of Cas12a itself to release individual guides from a single transcript and found V2 superior to V1 (27). Later, it was reported that a Cas12a guide architecture containing tRNA sequence instead of ribozymes worked best in wheat (28) and so we decided to test this in barley, designating the tRNA version V3.…”
Section: Cas12a Guide Architecture Optimisationmentioning
confidence: 99%
“… 107 Additionally, two new coding sequences, ttHsCas12a and ttAtCas12a+int, were discovered, helping further to boost the 90% mutagenesis in T0 barley plants. 108 Furthermore, heat stress and RNA-silencing suppressor are two other crucial techniques for enhancing the effectiveness of CRISPR genome engineering in plant species, including Nicotiana benthamiana , 109 , 110 Arabidopsis , 111 , 112 and Soybean. 113 , 114 These strategies will surely aid in increasing the coherence of the CRISPR-Cas system.…”
Section: Analysis Of Gene Editing Efficienciesmentioning
confidence: 99%